Peran Perencanaan SDM dan Pengarahan Dalam MSDM Strategik: Dampaknya Terhadap Produktivitas Karyawan Dengan Keterlibatan Karyawan Sebagai Mediasi - Nardo, Rio; Prayoga, Widi; Mulyana, Helmi; Yuniarsih, Tjutju (Bahtera Inovasi, 2025)
This study aims to look at the role of HR planning and direction in strategic HRM on employee productivity with employee engagement as mediation. This research is a correlational (associative) research with a quantitative approach. The data in this study were obtained using a questionnaire method. The data used is primary data. This study used 110 respondents as the research sample. The results of this study are that HR planning has an insignificant effect on employee productivity of Tour and Travel Companies in West Sumatra. Employee direction has a significant effect on employee productivity of Tour and Travel Companies in West Sumatra. Employee involvement mediates the effect of HR planning on employee productivity of Tour and Travel Companies in West Sumatra. Employee involvement mediates the effect of direction on employee productivity. Employee involvement has a positive and significant effect on employee productivity of tour and travel companies in West Sumatra. The employee involvement variable has the highest direct effect of 46.92% on productivity. This means that employee involvement in Tour and Travel Companies in West Sumatra can contribute the most compared to other variables to increase productivity.